(3fMh GdbdhHs - (3CHh GdbGSe YHO GdcQje GdbTjQj,J (B465 (3g` s ((3eMeO Hf bGSe Hf SYO Hf Mfjf GdSHGYi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bGd GdCSJGP CHh GdbGSe YHO GdcQje Hf ghGRf GdbTjQi QMeg Gddg GdfMh gh GdbUO Edi UhGH GdcdGe jbGd fMhJ fMhg Ci bUOJ bUOg afMh GdbdH GdbUO Edi MejO Gdbhd s
(3BNQgG (B:s
(3aef cGf NUGdg hUaGJg hUfYg aLeYJ LeY Gdbdjd hEf cGfJ NUGdg TQjaI aLeYJg LeY GdcKjQ hJNJda CMcGeg HGNJdGa ebOGQg agPg aUhd ai fMh GdbdhH CfTCJgG Ydi hLg GdEfLGR hHGddg Jhajb GdNdb CLeYjf hYdjg GdJcdGf hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG es
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1935s
Keywords: (3GdfMhs